Identification of Chilling Accumulation-Associated Genes for Litchi Flowering by Transcriptome-Based Genome-Wide Association Studies - Lu, Xingyu; Lü, Peitao; Liu, Hao; Chen, Houbin; Pan, Xifen; Liu, Pengxu; Feng, Lei; Zhong, Silin; Zhou, Biyan (Frontiers in Plant Science, 2022)
Litchi is an important Sapindaceae fruit tree. Flowering in litchi is triggered by low 19 temperatures in autumn and winter. It can be divided into early-, medium-, and late-flowering 20 phenotypes according to the time for floral induction. Early-flowering varieties need low 21 chilling accumulation level for floral induction, while the late-flowering varieties require high 22 chilling accumulation level. In the present study, RNA-Seq of the 87 accessions was 23 performed and transcriptome-based genome-wide association studies (GWAS) was used to 24 identify candidate genes involved in chilling accumulation underlying the time for floral 25 induction. 98155 high-quality single-nucleotide polymorphism (SNP) sites were obtained. 26 1411 significantly associated SNPs and 1115 associated genes (AGs) were identified, of 27 which 31 were flowering-related, 23 were hormone synthesis-related, and 27 were hormone 28 signal transduction-related. Association analysis between gene expression of the AGs and the 29 flowering phenotypic data was carried out, and differentially expressed genes (DEGs) in a 30 temperature-controlled experiment were obtained. As a result, 15 flowering-related candidate 31 associated genes (CAGs), 13 hormone synthesis-related CAGs, and 11 hormone signal 32 transduction-related CAGs were further screened. The expression levels of the CAGs in the 33 early-flowering accessions were different from those in the late-flowering ones, and also 34 between the flowering trees and non-flowering trees. In a gradient chilling treatment, 35 flowering rates of the trees and the CAGs expression were affected by the treatment. Our 36 present work for the first time provided candidate genes for genetic regulation of flowering in 37 litchi using transcriptome-based GWAS.